Relations between empathy and anxiety dimensions in inpatient adolescents. Issue 4 (4th July 2018) - Gambin, Malgorzata; Sharp, Carla
ABSTRACT: Background and objectives: A better understanding of the relationships between empathy and internalizing disorders is needed to plan therapeutic interventions for children and adolescents. Several studies have revealed positive relations of internalizing symptoms to personal distress and affective empathy. However, there is a lack of studies that take into account the multidimensional nature of anxiety in its relation to empathy. Design: Structural equation modeling was used to test the moderated mediation model of the relations between empathy, depression and anxiety dimensions and the moderating role of gender on these associations in inpatient adolescents. Method: A total of 403 inpatient adolescents aged 12–17 years completed the Basic Empathy Scale, the Multidimensional Anxiety Scale for Children, and the Beck Depression Inventory-II. Results: Affective empathy was positively related to all the anxiety dimensions – most strongly to separation/panic and humiliation/rejection anxiety, whereas cognitive empathy was negatively related to social and separation/panic anxiety. Relations between affective and cognitive empathy and anxiety were partly mediated by depressive symptoms. No evidence of a moderating role of gender has been found. Conclusions: Our results suggest that processes associated with empathy may play a role in the development or maintenance of anxiety symptoms.